Expression and bioregulation of the kallikrein-related peptidases family in the human neutrophil. Issue 6 (August 2015) - Lizama, Alejandro J; Andrade, Yessica; Colivoro, Patricio; Sarmiento, Jose; Matus, Carola E; Gonzalez, Carlos B; Bhoola, Kanti D; Ehrenfeld, Pamela; Figueroa, Carlos D
The family of kallikrein-related peptidases (KLKs) has been identified in a variety of immunolabeled human tissue sections, but no previous study has experimentally confirmed their presence in the human neutrophil. We have investigated the expression and bioregulation of particular KLKs in the human neutrophil and, in addition, examined whether stimulation by a kinin B1 receptor (B1R) agonist or fMet-Leu-Phe (fMLP) induces their secretion. Western blot analysis of neutrophil homogenates indicated that the MM of the KLKs ranged from 27 to 50 kDa. RT-PCR showed that blood neutrophils expressed only KLK1, KLK4, KLK10, KLK13, KLK14 and KLK15 mRNAs, whereas the non-differentiated HL-60 cells expressed most of them, with exception of KLK3 and KLK7. Nevertheless, mRNAs for KLK2, KLK5, KLK6 and KLK9 that were previously undetectable appeared after challenging with a mixture of cytokines. Both kinin B1 R agonist and fMLP induced secretion of KLK1, KLK6, KLK10, KLK13 and KLK14 into the culture medium in similar amounts, whereas the B1 R agonist caused the release of lower amounts of KLK2, KLK4 and KLK5. When secreted, the differing proteolytic activity of KLKs provides the human neutrophil with a multifunctional enzymatic capacity supporting a new dimension for its role in human disorders of diverse etiology.